1988
DOI: 10.1063/1.866780
|View full text |Cite
|
Sign up to set email alerts
|

The origin of the rotation in field-reversed configurations

Abstract: A review of experimental data suggests that particle loss and end shorting contribute together to the rotation of field-reversed configurations. Neither process can account for all available data by itself. An empirical scaling law based on both mechanisms is proposed that is consistent with all data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 19 publications
3
6
0
Order By: Relevance
“…Several observations are consistent with the end-shorting theory [318], such as increased values of T S for larger coil lengths [72,73,80,115,19,329,313] and fill pressures [92,130,114]. On the STP-L device, direct X (US) 50 [331]. The symbols are explained in Table III. measurements of edge layer rotation and of the delay in T S with guide fields at the ends of the theta pinch coil give partial support for the end-shorting process' [329] and also for particle transport [330].…”
Section: Origin Of the Rotationsupporting
confidence: 64%
See 1 more Smart Citation
“…Several observations are consistent with the end-shorting theory [318], such as increased values of T S for larger coil lengths [72,73,80,115,19,329,313] and fill pressures [92,130,114]. On the STP-L device, direct X (US) 50 [331]. The symbols are explained in Table III. measurements of edge layer rotation and of the delay in T S with guide fields at the ends of the theta pinch coil give partial support for the end-shorting process' [329] and also for particle transport [330].…”
Section: Origin Of the Rotationsupporting
confidence: 64%
“…It is the portion of the FRC that is MHD stable, and it may influence the unstable portion of the FRC, in particular for large separatrix pressures and axial flows near the ends. The edge layer may be the key to the origin and, therefore, the control of FRC rotation [318,352,331]. The edge layer also strongly influences the confinement properties of present FRCs.…”
Section: Discussionmentioning
confidence: 99%
“…4 As a destructive instability which limits the configuration's lifetime, rotational instability with toroidal mode number n = 2 is found only in experimentally generated FRCs. [6][7][8][9] More recently, numerical studies have also revealed a relationship to exist between ion spin-up and resistive decay of magnetic flux. It is generally believed that the configuration lifetime comes to an end due to contact of the core plasma with the chamber wall due to this elliptical deformation.…”
Section: Introductionmentioning
confidence: 99%
“…The idea is just to form adequately long-lived FRC plasma and subsequently translate and compress the target plasma quickly enough so that the FRC could not gain enough angular momentum to develop catastrophic deformation. If an FRC is formed in 3 s, it is to be translated for 60 cm at Alfven velocity cm s and compressed at speed of cm s in radial direction, the stable time of the target FRC is desired to be around s. The extrapolation of existing FRC scaling laws indeed suggests that such stable time is possible in the interested density regime [13], [15], [16]. Our current record FRC stable time in FRX-L is 10.5 s after a major effort of improving the main field performance declared a success (shown in Section V).…”
Section: Evolution Of the High-density Frc Plasmamentioning
confidence: 98%